STUDY THE PROCESS OF STUDENT RECRUITMENT FORM IN SCIENCE-BASED TECHNOLOGY DEMONSTRATION CLASSES UNDER THE SUPERVISION OF RAJAMANGALA UNIVERSITY OF TECHNOLOGY LANNA, CHIANG RAI - Srichai, Pongsook; Pichedboonkiat, Sirichom (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
The objectives of this research were 1) to comprehend the situation of student enrollment in a science-based technology demonstration classes and 2) to synthesize the appropriate model for the student enrollment process in a science-based technology demonstration class. The sample used in the research was Chief Executive Officers, curriculum heads, lecturers, mentors, staffs, and 30 students. The research tools were interviews and group focus discussions The statistics used for data analysis was content analysis. The research results were 1). Student enrollment situation: The university exhibits have strengths and opportunities as are selling points for parents and students, especially in specialized professional education, producing skilled graduates for industry, fostering personnel specialized knowledge, and having a modern laboratory. However, weaknesses and threats include the remote location of the university and increased competition in student enrollment. Proposed solutions involve policy setting and short-term and long-term enrollment strategies.) As for weakness and threats, the university’s location is far from the city and competition in student admissions has increased. Guidelines for solving recruitment problems by setting policies and planning strategies for student recruitment, both short-term and long-term planning. 2. Appropriate student enrollment process model suggested a diversified approach encompassing both online and offline methods with varied and easily accessible up-to-date information dissemination, contemporary communication language that is concise and clear, prompt response mechanisms, and proactive engagement with education institutions. Additionally, there is a necessity for a mobile unit for enrollment and a staff equipped who understand marketing strategies.